2013
DOI: 10.3109/13625187.2013.780202
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and bleeding profile of a combined oral contraceptive containing oestradiol valerate/dienogest: A pooled analysis of three studies conducted in North America and Europe

Abstract: E2V/DNG provides reliable contraceptive efficacy in women aged 18 to 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…The most recent study investigated a fertility control patch (patch) [8] while the previous studies investigated three different oral hormonal contraceptives (OC) [6,9, 10]. The estrogen component was either ethinylestradiol (EE) or estradiol valerate (E2V).…”
Section: Methodsmentioning
confidence: 99%
“…The most recent study investigated a fertility control patch (patch) [8] while the previous studies investigated three different oral hormonal contraceptives (OC) [6,9, 10]. The estrogen component was either ethinylestradiol (EE) or estradiol valerate (E2V).…”
Section: Methodsmentioning
confidence: 99%
“…We also examined other plausible values on the basis of a 10% rate of amenorrhea and a menstrual cycle frequency of 2 per month (mean of 0.95), and a 20% rate of amenorrhea and a menstrual cycle frequency of 3 per month (mean of 0.86) as assumed from the literature on menstrual bleeding pattern in women taking OCP. [44][45][46][47] The SD was fixed for all the 4 analyses and assumed to be 0.1 as reported in the Allen et al 39 The estimate of the treatment effect favored OCP (best case WMD −0.27, P < .01, 95% CI −0.33 to −0.21; worst case WMD −0.19, P < .01, 95% CI −0.25 to −0.13). However, this point estimate represents a 1-to 2-week difference in the frequency of menstrual cycles per month, which is equivalent to 3.24 menstrual cycles per year.…”
Section: Menstrual Regulationmentioning
confidence: 99%
“…4 Additionally, menstrual cycle bleeding patterns among healthy women taking OCP over a 12-month period may present with up to a 20% amenorrhea rate (defined as absent menstrual bleed for more than 2 months). [44][45][46][47] The observed amenorrhea could be due to poor compliance with OCP intake, reproductive organs immaturity, and other biological causes such as abnormal endometrial function. Abnormal endometrial function is apparent in other ways in PCOS as adult women with PCOS undergoing fertility treatments with proof of ovulatory cycles still express low pregnancy rates and higher spontaneous miscarriages rates, and menopausal women with PCOS are at higher risk for endometrial cancer.…”
Section: Figurementioning
confidence: 99%
“…E 2 V/DNG is an established contraceptive with a reduced-bleed profile 16,28,35. In a seven-cycle, multicenter, double-blind, double-dummy, randomized, controlled trial (RCT) in healthy women aged 18–50 years, E 2 V/DNG was shown to achieve shorter and lighter bleeding and resulted in a higher proportion of women without withdrawal bleeding compared with the monophasic combination of EE 20 μg/levonorgestrel (LNG) 100 μg administered in a 21/7-day regimen (21 days of hormone, followed by a 7-day HFI) (the proportion who experienced withdrawal bleeding per cycle through cycles 1–7 was 77.7%–83.2% with E 2 V/DNG and 89.5%–93.8% with EE/LNG [ P <0.0001 per cycle]) 28.…”
Section: Methodsmentioning
confidence: 99%